Informal Safety Communication of Construction Workers: Conceptualization and Scale Development and Validation - Cong, Weiyi; Xue, Hong; Liang, Huakang; Su, Yikun; Zhang, Shoujian (Frontiers in Psychology, 2022)
Existing studies have highlighted the importance of informal safety communication among workers at construction sites. However there is still a lack of empirically tested theoretical models with valid and reliable scales for describing and measuring construction workers’ informal safety communication (CWISC). Accordingly, this study aimed to fill this need by developing an instrument to assess the communication performance of construction workers. Four stages of scale development were described: construct formation, item generation, factor extraction through an Exploratory Factor Analysis (EFA) (n=219) and scale assessment through a Confirmatory Factor Analysis (CFA) (n=156). Using questionnaire data drawn from construction workers in China, the CWISC was verified to be a three-dimensional construct including Citizenship Safety Communication (CSC), Self-needed Safety Communication (SSC) and Participatory Safety Communication (PSC). The corresponding CWISC scale with 12 items was shown to have acceptable internal consistency reliability, as well as content, convergent and discriminant validity. The CWISC scale could serve as an instrument to assess and identify the weaknesses in informal safety communication performance of construction workers. In turn, this information could help supervisors implement appropriate management practices to those workers to enhance workplace informal safety communication. Related studies taking multidimensional CWISC into account were expected to carry out.